Investigation of optical properties of ternary Zn-Ti-O thin films prepared by magnetron reactive co-sputtering - Netrvalová, Marie; Novák, Petr; Šutta, Pavol; Medlín, Rostislav (Applied surface science, 2017)
[Display omitted] •Zn-Ti-O films were made by magnetron co-sputtering from metal targets in Ar/O2.•Optical properties were obtained by numerical fit of ψ(λ), Δ(λ) and T(λ) withal.•Spectral refractive indices and extinction coefficients exhibit two types of shapes.•Optical band gap energy grows with Ti content from 2.97 up to 3.78eV.•Optical properties indicate transition from ZnO to TiO2 amorphous structure. Zn-Ti-O thin films with different concentrations of titanium were deposited by reactive magnetron co-sputtering in a reactive Ar/O2 atmosphere from zinc and titanium targets. It was found that with increasing Ti content the structure of the films gradually changes from a fully crystalline pure ZnO wurtzite structure with a strongly preferred columnar orientation to an amorphous Zn-Ti-O material with 12.5at.% Ti. The optical parameters (spectral refractive index and extinction coefficient, optical band gap) and thickness of the films were analysed by the combined evaluation of ellipsometric measurements and measurements of transmittance on a UV–vis spectrophotometer. For evaluation of optical parameters was used Cody-Lorentz dispersion model.